Evaluation of a community-based intervention package to improve knowledge of obstetric danger signs, birth preparedness, and institutional delivery care utilization in Arba Minch Zuria District, Ethiopia: a cluster-randomized trial - Mekdes Kondale Gurara; Veerle Draulans; Yves Jacquemyn; Jean-Pierre Van Geertruyden (BMC, 2023)
Abstract Introduction Maternal healthcare utilization, particularly the institutional delivery, is disproportionately low in rural Ethiopia. This study aimed to evaluate the effectiveness of an integrated package of community-based interventions on the improved knowledge of obstetric danger signs, birth preparedness, and institutional delivery services utilization in rural areas of Gamo zone, southern Ethiopia. Methods We conducted cluster-randomized controlled trial (NCT05385380) from 2019 to 2021 at the Arba Minch Health and Demographic Surveillance System site. We randomly assigned the 10 kebele clusters to intervention and control arm. We used a package of interventions, which included providing information on safe motherhood via video and/or audio with a birth preparedness card for pregnant women, training for community volunteers and health extension workers, and improving maternity waiting home services. Women in the control arm received routine services only. We used generalized mixed-effects logistic regression models to evaluate the effectiveness of the intervention on the outcome variables. Results The study enrolled 727 pregnant women across the 10 clusters, with a 617 (84.9%) successful follow-up rate. The proportion of institutional delivery in the intervention arm was increased by 16.1% from 36.4% (174/478) at the baseline to 52.5% (224/427) at the endline (Adjusted odds ratio [AOR] for McNemar's Test = 1.5; 95% confidence interval [CI]: 1.1 to 2; p < 0.001). In the control arm, however, there was a 10.3% fall in the proportion of institutional delivery (from 164/249 to 105/190). Pregnant women who received the intervention were significantly more likely to give birth in a health institution than those who did not (AOR 2.8; 95% CI: 1.2, 6.4). Conclusion The study demonstrates that an integrated community-based intervention package that included video-based storytelling and upgrading maternity waiting homes increased institutional delivery care utilization among rural women. We recommend that audio-visual storytelling, starting during pregnancy and continuing postpartum, be incorporated into routine maternal healthcare services to address access to care inequalities in rural settings. Trial registration: The study protocol was registered in the clinicaltrials.gov with registry number NCT05385380.